Direct Utilization of Geothermal Energy: 2020 Worldwide Review - Lund, J.W.; Toth, Aniko (World Geothermal Congress 2020 Reykjavik, 2020)
A review of the worldwide application of geothermal energy for direct utilization as of 2020, and an update of the previous survey carried out in 2015. The presentation is based on papers and personal contacts with authors in 88 countries. The distribution of direct-use applications includes geothermal (ground-source) heat pumps, bathing and swimming, space and district heating, greenhouse heating, aquaculture pond and raceway heating, agricultural drying, industrial applications, and snow melting and cooling. Energy savings amounts to 600 million barrels of oil equivalent annually, preventing 78 million tons of carbon and 253 million tons of CO2 from being released to the atmosphere